The Future of Christian Realism: International Conflict, Political Decay, and the Crisis of Democracy - Gingles, Dallas; Mauldin, Joshua; Miles, Rebekah L. (Lexington Books, 2023)
In the world’s most developed democracies, anxiety about the future of democracy is palpable. The tension between moral aspiration and moral despair has reached a point of crisis. Christian realism arose during a similar time of crisis, when Reinhold Niebuhr used the insights of the Christian tradition to interpret the clash between democracy and totalitarianism. Beginning with Robin Lovin’s account of Christian realism as a nuanced blend of theological, moral, and political realisms, The Future of Christian Realism addresses fundamental topics in theology, ethics, and politics. The contributors come from different traditions, span five continents, and together present a case for the continuing relevance of Christian realism. By paying close attention to many of the most pressing moral challenges facing societies today, the authors illustrate and evaluate the enduring relevance of Christian realism.